Impact Assessment of Generative AI for Global Consulting Firm and Adaptation Strategy: SWOT/TOWS Analysis - Kazuya Nomura; Yudo Anggoro (Eduvest - Journal of Universal Studies, 2025)
The global consulting firm is urged to undergo a digital transformation trend driven by Generative Artificial Intelligence (AI), enabling the automation of complex tasks and enhancing decision-making, which overlaps with traditional consulting services. This study examines the impact of Generative AI on the global consulting firm by analyzing macro trends of Generative AI and the core competencies of the global consulting firm, inviting business owners from several industries and Generative AI consultants for interviews. Adopting a qualitative method, this research generates a SWOT analysis and proposes an adaptation strategy for the global consulting firm. Findings reveal that Generative AI can automate some tasks, such as analytics, but cannot fully replace traditional consulting due to functional limitations. Challenges—including data security, unstandardized processes, and workforce resistance—hinder adoption, which means it cannot substitute traditional consulting services immediately. The global consulting firm should leverage its strengths—AI expertise, global partnerships, and comprehensive service—to support client challenges as business opportunities.